Building 3D modelling of UiTM Arau Perlis Campus using Agisoft software / Nur Farahizyan Mohd Aseri - Mohd Aseri, Nur Farahizyan (2019)
3 dimensional modelling or known as 3D modelling is one of the latest technology in surveying fields. The creation of 3D modelling can be differing according to the purpose and user needs. One of the methods that can be used to produce 3D modelling is by using Unmanned Aerial Vehicles (UAV) that is also one of the branches in photogrammetry techniques. However, choosing the suitable software can be a challenging task in building 3D modelling especially for the large campus area. As the second largest UITM Campus in Malaysia, UITM Arau Perlis Campus offer variety of building structure and landscape. The Aim and objective of this study is to visualise the 3D modelling of the campus using Agisoft Software and also to imposed in the Google Earth. As a result of this study the capability of this study is discovered. This study hopefully be able to help in understanding the Agisoft Software and how it works in modelling buildings.